Rewiring the Brain Through the Gut: Insights into Microbiota–Nervous System Interactions - Ilinca Savulescu-Fiedler; Serban-Nicolae Benea; Constantin Căruntu; Andreea-Simona Nancoff; Corina Homentcovschi; Sandica Bucurica (Current Issues in Molecular Biology)
The gut-brain axis (GBA) represents an operant acting in a two-direction communication system between the gastrointestinal tract and the central nervous system, mediated by the enteric nervous system (ENS), vagus nerve, immune pathways, and endocrine signaling. In recent years, evidence has highlighted the pivotal role of the gut microbiota in modulating this axis, forming the microbiota-gut-brain axis (MGBA). Our review synthesizes current knowledge on the anatomical and functional substrates of gut-brain communication, focusing on interoceptive signaling, the roles of intrinsic primary afferent neurons (IPANs) and enteroendocrine cells (EECs) and the influence of microbial metabolites, including short-chain fatty acids (SCFAs), bile acids, and indoles. These agents modulate neurotransmission, epithelial barrier function, and neuroimmune interactions. The vagus nerve serves as a primary pathway for afferent sensory signaling from the gut influenced indirectly by the ENS and microbiota. Dysbiosis has been associated with altered gut-brain signaling and implicated in the pathophysiology of disorders ranging from irritable bowel syndrome to mood disorders and neurodegeneration. Microbial modulation of host gene expression via epigenetic mechanisms, including microRNAs, adds another layer of complexity. The gut has a crucial role as an active sensory and signaling organ capable of influencing higher-order brain functions. Understanding the MGBA has significant implications for new therapeutic interventions targeting the microbiome to manage neurogastroenterological and even neuropsychiatric conditions.